ON STRENGTHENING INTERETHNIC HARMONY AND TOLERANCE IN NEW UZBEKISTAN PUBLIC POLICY - Babajanova Diloram; Yuldasheva Gulnora Kamilovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article covers the most important aspects of the state policy on the issue of interethnic harmony in multinational Uzbekistan, the issues of mutual respect, kindness and stability of the atmosphere of harmony between the people of different nationalities residing here. No matter any political, social and negative circumstances have occurred at all times of the past, the Uzbek people have shown their tolerance and high-ranking qualities, always maintained national values such as friendly relations with different nations, Hospitality, which was instrumental in the constant existence of all nations and peoples in this homeland, and in the formation of a single family feeling, manifesting itself in every way. It included issues of improving interethnic relations of peoples, stability between the turfa Nations, and interreligious tolerance